2022
DOI: 10.1002/pits.22645
|View full text |Cite
|
Sign up to set email alerts
|

Learning under stress: The moderating role of future time perspective

Abstract: We investigated the relationship between students' perceived stress and investment in learning and tested the role of future time perspective (FTP) as a moderator. We expected that FTP would serve as a protective factor in the association between students' perceived stress and investment in learning. Perceived stress was gauged by assessing students' mathematics anxiety related to class, learning, and tests, and investment in learning was gauged by measuring investment in learning with respect to mathematics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…The comprehensive goal of the study was to attempt to determine whether there is a correlation between temporal orientation and a tendency towards burnout syndrome symptoms. Various previous research has shown strong correlations between temporal orientation and stress [ 24 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The comprehensive goal of the study was to attempt to determine whether there is a correlation between temporal orientation and a tendency towards burnout syndrome symptoms. Various previous research has shown strong correlations between temporal orientation and stress [ 24 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, guided by the active learning hypothesis, when job demands exceed the resources of individuals, they may perceive higher job demands and stronger threats, and then actively generate learning behaviors to obtain more resources to cope with stress ( Karasek and Theorell, 1990 ; Daniels et al, 2009 ). Further, given that learning behavior is not only a main way to cope with stress ( Andre et al, 2022 ) but also an important path for improving innovation performance ( Holman et al, 2012 ), learning behavior may play a mediating role in the J-shaped relationship between time pressure and innovation performance. Therefore, it is essential to identify the mediating effect of learning behavior in order to bridge this gap.…”
Section: Introductionmentioning
confidence: 99%